2019
DOI: 10.22159/ajpcr.2019.v12i7.33211
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Plant-Mediated Metal Nanoparticles: The Role of Polyphenols

Abstract: The use of metal nanoparticles (MNPs) in various fields is increasing day-by-day leading to a genuine concern about the issues related to their environmental and biological safety. The major approaches for the synthesis of NPs include physical and chemical methods which are expensive and hazardous to health in addition to being toxic to the environment. This review highlights the potential of plant extracts to carry out the synthesis of MNPs with a special emphasis on the role of flavonoids in nanosynthesis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…Given the predominance of polyphenols like flavonoids and xanthones in fresh coconut inflorescence sap, it could be assumed that these compounds could be mainly involved in synthesis of NPs. Many studies have reported the role of polyphenols in the promotion of green synthesis of metal NPs (Tao et al, 2016;Jigaysa and Rajput, 2018;Singh et al, 2019;Latif et al, 2019).…”
Section: Metabolomic Profiling Of Coconut Inflorescence Sapmentioning
confidence: 99%
“…Given the predominance of polyphenols like flavonoids and xanthones in fresh coconut inflorescence sap, it could be assumed that these compounds could be mainly involved in synthesis of NPs. Many studies have reported the role of polyphenols in the promotion of green synthesis of metal NPs (Tao et al, 2016;Jigaysa and Rajput, 2018;Singh et al, 2019;Latif et al, 2019).…”
Section: Metabolomic Profiling Of Coconut Inflorescence Sapmentioning
confidence: 99%
“…The sharp band at 2973 cm -1 and 2881 cm -1 represent the stretching of the C-H bond. The band at 1046 cm -1 may be considered as the -C-O group of the polyphenols such as flavones, polysaccharides and terpenoids [34][35][36]. The FTIR spectra after reduction of turmeric crude extract showed peak at 3334 cm -1 belongs to the -OH group which, in this case, can be attributed to the phenolic compounds of turmeric extract.…”
Section: Resultsmentioning
confidence: 88%
“…asiatica is known to contain a wide variety of phytochemicals, the secondary metabolites, which signifies the tremendous medicinal importance of this ancient herb. It has been reported to contain the phytochemicals including triterpenoids or saponins, volatile and fatty acids, glycosides, flavonoids, alkaloids, and certain vitamins and free amino acids (Jamil et al, 2007;Latif et al, 2019;Orhan, 2012). A concise summary of the important phytochemical constituents of C. asiatica has been presented in Table 2 along with representative examples of each main group of C. asiatica phytochemicals.…”
Section: Phytochemical Constituentsmentioning
confidence: 99%